The Role of Employee Engagement as a Mediator in the Influence of Perceived Organizational Support and Talent Management on Employee Performance in the Regional Secretariat of Wonosobo Regency - Rahmawati, Ferika Dewi; Liana, Lie (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of perceived organizational support and talent management on employee performance with employee engagement as a mediating variable in the Civil Service (ASN) at the Regional Secretariat of Wonosobo Regency. This study uses a quantitative approach with a survey method, involving a population of 118 respondents. The data were processed using SPSS software version 26. Data analysis techniques included respondent description, variable description, validity test, reliability test, F test, R2 test, t test, and Sobel Test. The results showed that perceived organizational support had a positive effect on employee engagement and talent management had a positive effect on employee engagement. Perceived organizational support does not affect employee performance, talent management has a positive effect on employee performance, and employee engagement has a positive effect on employee performance. Employee engagement mediates the effect of perceived organizational support on employee performance, and employee engagement mediates the effect of talent management on employee performance.